2016
DOI: 10.1108/yc-07-2015-00536
|View full text |Cite
|
Sign up to set email alerts
|

Peer influence strategies in collectively consumed products (events and festivals): an exploratory study among university students

Abstract: , 2016. Peer influence strategies in collectively consumed products: events and festivals, Young Consumers (forthcoming) ABSTRACT Purpose: The paper examines peer influence in the context of purchasing collectively consumed products. The particular focus of the paper is on strategies used by university students for persuasion and resistance when attending events & festivals.Methodology: Five females and three males studying for a degree in the UK were interviewed. Independent analysis of the interview transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
0
5
0
2
Order By: Relevance
“…Another study on social media shopping behavior (Muralidharan and Men, 2015) demonstrated that users were affected by peers in China and the United States, despite cultural differences between the two groups. Scully and Moital (2016) and Sherman et al (2018) also suggested that peer influence is particularly intense among university students due to the proximity of friends within that environment. These findings lead us to Hypothesis 4: H4.…”
Section: Peer Influence and Attitude Towards Mobile App Usementioning
confidence: 99%
“…Another study on social media shopping behavior (Muralidharan and Men, 2015) demonstrated that users were affected by peers in China and the United States, despite cultural differences between the two groups. Scully and Moital (2016) and Sherman et al (2018) also suggested that peer influence is particularly intense among university students due to the proximity of friends within that environment. These findings lead us to Hypothesis 4: H4.…”
Section: Peer Influence and Attitude Towards Mobile App Usementioning
confidence: 99%
“…Information in an online community can significantly impact young consumers (Duffett, 2017), as they are prone to be influenced by other members of a social network (Christensen and Schiaffino, 2014). In addition, peer influence also significantly contributes to young consumers’ purchasing intentions (Scully and Moital, 2016; Opoku, 2012). Thus, the information generated from an online community plays an important role in influencing young consumers’ attitudes and behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…Sehingga lingkungan teman sebaya yang semakin baik akan membuat financial management behavior otomatis menjadi semakin baik pula. Penelitian ini selaras dengan penelitian terdahulu Bamforth (2018), Diningrum (2018), Kadir & Jamaluddin (2020), Scully & Moital (2019) yang menyatakan bahwa terdapat pengaruh positif antara teman sebaya dengan financial management behavior seseorang.…”
Section: Teman Sebaya Mempengaruhi Financial Management Behavior Siswaunclassified
“…Hal ini selaras dengan penelitian Bamforth (2018) teman sebaya mempengaruhi sesorang dalam hal mengelola keuangannya. Juga penelitian Scully & Moital (2019) yang menyebutkan bahwa perilaku seseorang dalam mengkonsumsi suatu barang dipengaruhi oleh teman sebaya. Peer influence memiliki peran strategis dalam mengembangkan literasi keuangan, perilaku keuangan dan pengetahuan keuangan (Yanto et al, 2021).…”
unclassified